HEALTH EDUCATION ADOLESCENT REPRODUCTIVE (KRR) IN EFFORT HEALTH SCHOOL (UKS) DEPENDENT BEHAVIOR PREMARITAL SEXUAL YOUTH WOMAN (Study in 5 SMP Negeri at District Jombang) - Rusma Indriamawanti Ningtias; . Muarrofah; . Baderi (Jurnal Keperawatan, 2014)
Less knowledge of health reproductive provide opportunied to did behavior premarital seksual. It can protect by UKS provided health education reproductive it. Purpose this was know correlation health education adolescent reproductive (KRR) in effort health school toward behavior premarital sexual it, in study five junior high school country district Jombang. Research uses approach Analitic with Cross Sectional. Pupulation risert all students at eighth class in five junior high school country district Jombang, amount to 718 students. Sampling using probability proportionate the type of simple random sampling. The totaled sample 215 students. Independent variable health education adolescent reproductive (KRR) in effort health school (UKS) and dependent variable behavior premarital sexual youth woman. Research instrument used quesionnairs. Procesing data with Editing, Coding, Scoring and Tabulating were analized used a Mann Whitney with a error rate α = 0,05. Result almost half 104 (48,4%) KRR education in UKS enough and most of the 119 (55,3%) behavior premarital sexual aldolescent negative. Based calculation statistic test of Mann Withney the values ρ = 0,00, ρ < α. H1 was accepted. There conlasion from this research was find correlation health education adolescent reproductive (KRR) in effort health school (UKS) toward behavior premarital sexual in five junior high school country district Jombang.Keywords : behavior premarital sexual, aldolescent, effort health school, health education reproductive